P3 Pilot study to test the feasibility of a psychological support workshop for patients newly diagnosed with Idiopathic Pulmonary Fibrosis (IPF) and their families. (12th November 2015) - Cove, J; Russell, AM; Wright, J; Hogben, C; Kokosi, M; Mak, V; Chua, F; Wells, A; Doyle, AM; Renzoni, E
Abstract : Introduction: IPF is associated with a poor prognosis, high symptom burden and limited treatment options. Psychological reactions are comparable to those seen in cancer patients, yet support services for IPF patients are less well developed. There is an urgent demand to develop Interstitial Lung Disease (ILD) services that better support the psychological needs of IPF populations. The aim of this pilot study is to characterise the psychological needs of both patients and carers and to test the feasibility of a workshop approach. Methods: Consultant ILD physicians identified patients recently diagnosed with IPF at our Unit, and referred them to the clinical nurse specialist. Patients were invited to attend a half day workshop with an accompanying 'guest'. The workshop, led by a clinical psychologist, included didactic teaching, interactive discussions and experiential learning. Topics covered coping with low mood and anxiety, symptom control and transitions towards the end of life. Four members of the clinical team were present throughout as observers and to provide support. Demographic information; PHQ-9 and GAD-7 scores were collected (Table 1 ). Participants completed a semi-structured questionnaire at the end of the workshop. Framework analysis identified themes around the impact of attending the workshop. Results: 13 patients and 16 family members attended the workshop. Participants reported benefiting from peer support; identifying with others. They felt emotionally supported through sharing experiences and appreciated the chance to learn about practical ways of managing symptoms and accessing other sources of support. All respondents said they would recommend the workshop to others diagnosed with IPF and their families. Participants reported that more medical information about IPF, its progression and prognosis would have been useful. Suggestions included requests for a larger venue and more information on oxygen. Conclusions: Preliminary data suggests attendance at a workshop addressing psychological issues is feasible and is perceived to be a positive experience by patients diagnosed with IPF and their families. Future workshops will include more time for group discussion to facilitate peer support. A further two workshop are planned in July and September. Successive evaluations will continue to inform the development of subsequent workshops.